"Only God Can Judge Me": Faith, Trauma, and Combat. (January 2015) - Solomon, Nathan
The particular trauma of combat is a special subset of trauma for those who experience it (the "Sent"), those who call for it (the "Senders"), and those who minister in the midst of it (the "Liminals"). The trauma experiences of veterans are a unique opportunity for the church to embrace its own liminal calling.